Internet use, depression, and cognitive outcomes among Chinese adolescents. Issue 2 (20th December 2021) - Zhou, Muzhi; Ding, Xuejie
Abstract: This study provides new evidence on how the growingly significant digital life shapes Chinese adolescents' cognitive and mental health outcomes based on their gender, parental education, and geographical location. Using the China Education Panel Survey, a nationally representative survey following 12–15‐year‐old students in 2013 and 2014, and individual fixed‐effect models, we find that more time spent on the Internet is associated with higher self‐reported depression scores. This negative impact on mental health is more substantial for girls, those with less‐educated parents, and those living outside the city center. The link between Internet use and cognitive development is almost null. Time spent online negatively affects Chinese young adolescents' subjective well‐being but has little impact on their cognitive development. The link between Internet use time and subjective well‐being also depends on gender, parental education, and the geographical location of those adolescents. The heterogeneous impacts of Internet use time offer crucial new evidence to the multiple dimensions of the digital divide among adolescents in China.